THE IDEOLOGY OF INDONESIAN TRANSLATION IN THE “THE BOGEY-BEAST” FAIRYTALE - Egi Raputri (Universitas Muhammadiyah Prof. DR. HAMKA, 2021)
Translation plays an important role in assisting the audiences for understanding the information of the writer or speaker. In order to avoid misunderstanding, the translator needs to consider the methods they used. It should be depended on the object to be translated and the addressee. Therefore, this study aimed at identifying the translation methods and the translation ideology in the translation of an English fairytale entitled “The Bogey-Beast” retold by Flora Annie Steel (1922). This fairytale translated in Indonesian by Pustaka Bahasa Inggris. This study employed the theory of translation ideology proposed by Venutti (1995). Besides, in investigating the translation method used by the translator, this study employed the translation method theory constructed by Newmark (1988). Through descriptive qualitative approach, the findings of this study revealed that the translator used six methods such as word-for-word, literal, faithful, semantics, free, and idiomatic translation. Meanwhile, semantics translation method was the dominant method used by the translator. Thus, it can be concluded that the translator of Indonesian version “The Bogey-Beast” fairytale tends to the foreignization ideology. Keywords: translation, fairytale, translation method, translation ideology